Proteomic Profile Analysis of Synovial Fluid in Patients With Anterior Cruciate Ligament Tears. Issue 11 (September 2022) - Brophy, Robert H.; Cai, Lei; Zhang, Qiang; Townsend, R. Reid; Rai, Muhammad Farooq
Background: Anterior cruciate ligament (ACL) tears are associated with posttraumatic osteoarthritis, but the early biological changes that initiate joint degeneration after this injury are not well characterized. ACL tears typically result in effusion in the knee, which may provide insight into the initial response of the joint to injuries. Hypothesis: Patient- and injury-specific factors are associated with the proteomics of synovial fluid in knees with ACL tears. Study Design: Descriptive laboratory study. Methods: Synovial fluid was collected from 105 patients (38 male, 67 female) with an acute traumatic ACL tear. Patient- and injury-specific factors such as age, sex, body mass index, time from injury, presence/absence of concomitant meniscal tears, and location of concomitant bone bruises (if present) were recorded. The protein concentration of synovial fluid was measured, followed by benchmarking of samples for multi-affinity high-abundance protein depletion. An isotropically labeled high-resolution nano-liquid chromatography with tandem mass spectrometry–based proteomic approach was used to determine the synovial fluid protein profile. Data were processed, quality controlled, and analyzed computationally for each patient and injury factor. Results: The proteomics of synovial fluid from ACL tears was associated with patient sex, injury pattern, and location of bone bruises but not with patient age, body mass index, or time from injury. Knees with an isolated ACL tear had higher glutathione peroxidase 1 (GPX1) and plastin 3 levels than knees with an ACL tear and meniscal tear. A bone bruise on the lateral femoral condyle was associated with elevated leptin and glucose-6-phosphate dehydrogenase (G6PD) levels. A bone bruise on the lateral tibial plateau was associated with decreased GPX1 levels. Male patients had higher matrix metalloproteinase 9 and lower G6PD levels than female patients. Conclusion: Patient sex, injury pattern, and bone bruise location were important determinants of the proteomic profile of effusion resulting from ACL tears. Clinical Relevance: Longitudinal follow-ups to see if and how proteomic differences relate to clinical outcomes and mechanistic studies to assess the role that specific proteins play in the joint are warranted. Ultimately, these investigations could lead to better approaches to predict clinical outcomes and identify possible interventions to optimize outcomes in these patients.